(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The inscription analysed in this paper contains a brief and fragmented text that most likely can be reconstructed as a new Iberian per-sonal name: [la]kubalka[r]. Its palaeographic chronology is compatible with the used during the second and first centuries B.C. Although strictly the chronology of the settlement where it has appeared, a wine and amphorae production centre, covers the last decade of first century B.C., until the early 70s of the first century A.D., the presence of materials out of context from previous chronologies, especially of the second and first centuries B.C. suggests the existence of an Iberian settlement in the El Mujal-El Roser abandoned in the late first century B.C. and from which probably proceed the inscription studied in this article.